A Nanoreview of Nanoscience. Issue 2 (3rd April 2022) - Ayers, Meredith
ABSTRACT: Research in nanoscience has increased rapidly since 2002. Some scientists anticipate that nanoscience will lead to advances in health, material sciences, and technology that would lead to a more environmentally friendly and sustainable future for the planet. A search performed in Web of Science in June 2021 showed over 1, 000, 000 items are available on the broad topic. Researchers new to the field will need help navigating the copious literature and narrowing their searches to get the few relevant articles that they need. After a brief review of the science to demonstrate the field's depth and diversity, the article will offer an overview of the literature to help researchers find the best starting point for searching.